2006
DOI: 10.1007/s11664-006-0154-5
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, creep properties, and failure mechanism of SnAgCu solder joints

Abstract: The effect of microstructure on the creep properties and the failure mechanism of SnAgCu solder joints was studied. Single overlap shear specimens made of FR-4 printed circuit boards (PCBs) with organic solderability preservative (OSP), NiAu, and immersion Sn surface finish were reflow-soldered with hypoeutectic, eutectic, and hypereutectic SnAgCu solder paste. Creep tests of the solder joints were performed at 85°C and 105°C under constant load. The effect of microstructure on the creep behavior of the joints… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…), commensurately reducing joint fracture toughness. 9,10,19,20 Secondly, solder composition changes may promote the formation of brittle interfacial IMCs, leading to an increase of the propensity for crack propagation through the IMC layer and reduction of joint toughness; for example, an increase in the Ag content of SAC solders promotes formation of brittle (Ni,Cu) 3 Sn 4 in addition to (Ni,Cu) 6 Sn 5 * at solder-electroless Ni-P pad interfaces, resulting in an increase in the proportion of IMC fracture in SAC305 and SAC405, as compared with SAC105. 21 Thirdly, the proportion of IMC fracture increases with an increase in the strength of the solder; for example, an increase in the Ag content of SAC solder makes it harder without altering the thickness or the composition of the IMC layer at the solder/NiAu-pad interface, and yet reduces fracture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…), commensurately reducing joint fracture toughness. 9,10,19,20 Secondly, solder composition changes may promote the formation of brittle interfacial IMCs, leading to an increase of the propensity for crack propagation through the IMC layer and reduction of joint toughness; for example, an increase in the Ag content of SAC solders promotes formation of brittle (Ni,Cu) 3 Sn 4 in addition to (Ni,Cu) 6 Sn 5 * at solder-electroless Ni-P pad interfaces, resulting in an increase in the proportion of IMC fracture in SAC305 and SAC405, as compared with SAC105. 21 Thirdly, the proportion of IMC fracture increases with an increase in the strength of the solder; for example, an increase in the Ag content of SAC solder makes it harder without altering the thickness or the composition of the IMC layer at the solder/NiAu-pad interface, and yet reduces fracture resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [16] found that the creep rupture mode for two types of solder joints is inter-granular through grain boundary sliding and boundary voids growth. Sundelin et al [17] thought that the tip of ductile on the rupture surface was formed in the Sn-rich area, leaving aside the eutectic network structure Sn ? Ag 3 Sn.…”
Section: Introductionmentioning
confidence: 99%
“…1 Potential replacements for tin-lead include Sn-Ag-Cu, Sn-Ag, Sn-Cu, Sn-Zn, Sn-Bi-Ag, and Sn-In-Ag. 2 While these alloys have proven suitable for application temperatures up to 125°C, many electronics applications in the aerospace, automotive, and oil and gas drilling sectors require application temperatures in excess of 150°C. Deformation in these high-temperature environments due to creep is the main problem with these alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Deformation in these high-temperature environments due to creep is the main problem with these alloys. 3 Sn-3.8Ag-0.7Cu (SAC) is generally the most recommended lead-free soldering alloy for reflow soldering because of its low melting point, mechanical strength, adequate wetting properties, and good availability, 2,4,5 and hence this paper concentrates on nanoparticle additions to the basic SAC alloy.…”
Section: Introductionmentioning
confidence: 99%